On Noncompact Fractional Order Differential Inclusions with Generalized Boundary Condition and Impulses in a Banach Space - Irene Benedetti; Valeri Obukhovskii; Valentina Taddei (Journal of Function Spaces)
We provide existence results for a fractional differential inclusion with nonlocal conditions and impulses in a reflexive Banach space. We apply a technique based on weak topology to avoid any kind of compactness assumption on the nonlinear term. As an example we consider a problem in population dynamic described by an integro-partial-differential inclusion.